(untitled) (REMUNOM, 2026)
This study analyzed the perceptions of the school community in an educational unit located in a traditional territory in the municipality of Moju, in the Amazon region, regarding the democratic management of the school council, understood as a mechanism for collective participation and decentralization of institutional decision-making. The main objective was to understand how different school actors—parents, students, teachers, and staff—interpret and experience participatory practices within the school context. To achieve this, semi-structured interviews were conducted with representatives from different segments of the school community, allowing for the collection of narratives, experiences, and perspectives related to the council’s performance. The findings indicate that most participants demonstrate a conceptual understanding of democratic management and acknowledge its importance in promoting inclusion, dialogue, and shared responsibility in decision-making processes. It was also observed that parents and teachers participate more regularly in meetings, contributing suggestions for school improvement. However, significant tensions emerged, particularly regarding student participation, which was perceived as limited. Additionally, structural and communicational challenges were identified, such as lack of time, insufficient transparency, and weak communication channels, which hinder effective participation. The study concludes that although democratic management is valued by the school community, its full implementation requires strategies that enhance transparency, improve communication, and ensure equitable participation of all groups, especially students. Thus, strengthening the school council as a deliberative body depends on overcoming cultural and organizational barriers.